Corrosion Inhibition of Mild Steel in Citric Acid by Aqueous Extract of Piper Nigrum L. Issue 1 (2012) - Matheswaran, P.; Ramasamy, A. K.
Abstract : The inhibition efficiency (IE) of an aqueous extract of Piper Nigrum L. in controlling corrosion of mild steel at pH 12 has been evaluated by weight loss method in the absence and presence of inhibitor in citric acid medium at different concentration. The result showed that the corrosion inhibition efficiency of these compounds was found to vary with the different concentration at two hour time interval at room temperature. Also, it was found that the corrosion inhibition behaviour of Piper Nigrum L. is greater in 2 N Citric acid than 1 N Citric acid medium. So Piper Nigrum L. can be used has a good inhibitor for preventing mild steel material which is used in many construction purpose.